The Impact of Economic Growth, Oil Price, and Financial Globalization Uncertainty on Financial Development: Evidence from Selected Leading African Countries - Farouq, Ibrahim Sambo; Sulong, Zunaidah (International Journal of Business, Economics and Management, 2020)
A lack of financial scope has for long hinders the efficiency of the financial system in the African continent. In this paper, we investigate the effects of economic growth, oil price, and financial globalization uncertainty on financial development in six selected leading African countries, covering the period between 1976–2018. After the preliminary tests that confirmed the application of heterogeneous panel techniques, the paper was able used Larsson co-integration to establish the presence of long-run relationship among the variables, which the co-integration result confirms that. We further deployed Dynamic Common Correlated Effect (DCCE) for the elasticity estimation. The findings of the study based on the empirical analysis observed that both economic growth, financial globalization uncertainty and oil price affects the financial system of the sampled countries positively and statistically significant. We therefore, recommends that the sampled economies’ policymakers should strategize and come up with suitable policies that will promote substantial economic growth, attracts more foreign investors and continue to be resilient in times of financial shocks.